Revelation and authority: Sinai in Jewish scripture and tradition - Sommer, Benjamin D. (The Anchor Yale Bible reference library, 2015)
Participatory theories of revelation -- Artifact or Scripture? -- Revelation at Sinai, maximalist and minimalist approaches -- Command and law in the participatory theology of revelation -- Scripture as tradition, and tradition as Scripture -- Revelation event, process, and eternity -- A modern Jewish approach to Scripture -- Innovation, continuity, and covenant.